Analisis Lereng Villa Fumida Desa Kuta Kampung Babakan Megamendung Bogor - Riyansyah, Arya Adika (UNISSULA Semarang, 2024)
The rainy season that occurs in parts of Indonesia is a season where there is great concern about landslides, such as in Lampung and in Bandung, several luxury houses in a housing complex experienced very serious landslides, even the house right on the slope seemed to disappear into the ground, resulting in several Other houses were also badly damaged. As a result of this incident, the homeowner suffered major losses due to the landslide. The method for analyzing landslides or slopes is currently very easy to learn, because today's technology is increasingly sophisticated, it can be analyzed using software, such as geostudio, plaxis, and so on. Meanwhile, for this research, we used geostudio software Seep/W and Slope/W, where we analyzed data from the field with rainy conditions for 6 hours using Seep/W, and we analyzed the SF using Slope/W.The results of the analysis of rainwater infiltration on the slopes show that the safety factor is decreasing due to rain for 6 hours. On the slope before it rains, the slope safety factor value is 1.296. Meanwhile, in conditions of 6 hours of rain, the slope safety factor decreases by 6.48% to 1.212. So from table 2.3 it can be classified that the initial slope before the rain has a value of > 1.25, which means that the landslide intensity rarely occurs or the slope is stable. Meanwhile, after it rains, the slope becomes critical because the safety factor value is <1.25.Reinforcement of stone masonry retaining walls has a safety factor value against overturning of 3.20 or ≥ 1.5, which means that the retaining wall is safe against overturning. Meanwhile, the safety factor value against sliding is 24.72 or ≥ 1.5, which means that the retaining wall is safe against shifting. The Qmax value is 1.21 kN/m2 and Qall is 90.45 kN/m2, which means that the bearing capacity of the soil is able to withstand the stone masonry retaining wall because Qmax < Qall. The results of the analysis of rainwater infiltration on the slopes and retaining walls of river stone masonry show that the safety factor before rain has an SF value of 1.627. Meanwhile, under 6 hours of rain, the SF value experienced a small decrease of 0.001 to 1.626. Or around 0.06%. From the research results, it was found that the modeling with the presence of DPT resulted in water entering the slope not penetrating the retaining wall, and flowing directly to the surface of the retaining wall, so that no water rose to the surface of the slope, and the SF value could be said to be stable. Key words : infiltration analysis, slopes, landslides